African Economic History (JSTOR)
African Economic History is an annual publication designed to publish scholarly research in all aspects of the economics of the African past, including historiography, with an emphasis of sub-Saharan and colonial and post-colonial themes. Included are agricultural economics, manufacturing, short- and long-distance trade, including the slave trade, the introduction of new technologies, monetization, financing, and the like. Papers may be in either English and French.
Keywords: African Studies